2006
DOI: 10.1073/pnas.0508875103
|View full text |Cite
|
Sign up to set email alerts
|

Viral delivery of glial cell line-derived neurotrophic factor improves behavior and protects striatal neurons in a mouse model of Huntington’s disease

Abstract: Huntington's disease (HD) is a fatal, genetic, neurological disorder resulting from a trinucleotide repeat expansion in the gene that encodes for the protein huntingtin. These excessive repeats confer a toxic gain of function on huntingtin, which leads to the degeneration of striatal and cortical neurons and a devastating motor, cognitive, and psychological disorder. Trophic factor administration has emerged as a compelling potential therapy for a variety of neurodegenerative disorders, including HD. We previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 46 publications
(48 reference statements)
5
43
1
Order By: Relevance
“…[46][47][48] Although several other interesting studies have demonstrated potential neuroprotective properties of different factors investigated in the context of HD, none of these factors have afforded the same dramatic protection against excitotoxicity as is in the transgenic HD mouse models we have described in this review article (see e.g. Saydoff et al, 49 Dedeoglu et al, 50 McBride et al, 51 Jin et al 52 and Ferrante et al 53 ).…”
Section: Possible Mechanisms Involved In Huntingtin-mediated Resistancementioning
confidence: 87%
“…[46][47][48] Although several other interesting studies have demonstrated potential neuroprotective properties of different factors investigated in the context of HD, none of these factors have afforded the same dramatic protection against excitotoxicity as is in the transgenic HD mouse models we have described in this review article (see e.g. Saydoff et al, 49 Dedeoglu et al, 50 McBride et al, 51 Jin et al 52 and Ferrante et al 53 ).…”
Section: Possible Mechanisms Involved In Huntingtin-mediated Resistancementioning
confidence: 87%
“…GDNF has been shown to protect both dopamine neurons and striatal neurons undergoing degeneration in models of Parkinson's and Huntington's disease when delivered directly to the striatum of primates and rodents using in vivo gene therapy approaches (14,16,19) Ex vivo approaches in which stem cells are modified to release GDNF and then transplanted offer an interesting alternative that does not require the injection of live virus to the brain. However, to achieve widespread delivery of GDNF, it will be necessary for the cells to migrate and integrate across wide areas.…”
Section: Discussionmentioning
confidence: 99%
“…First, compared with glial cells, lower and impaired neuronal ubiquitin-proteasome system activity, which plays a critical role in clearing misfolded proteins [18] , may account for the preferential accumulation of misfolded Htt in neurons as well as their selective vulnerability [19][20][21] . Second, the expression of mutant huntingtin in glial cells, which could clear excess excitatory neurotransmitters from extracellular space, contributed to neuronal excitotoxicity [2,5,22,23] .…”
Section: Recovery Of Glt-1 Expression and Function By Rapamycinmentioning
confidence: 99%